Ballistic performance of lightweight ceramic-metal composite armour plates under blunt projectile impact - Hasan Aftab Saeed; Yasser Riaz Awan; Hamza Saleem Khan; Abdur Rehman Mazhar; Shahid Aziz; Dong-Won Jung (Composites Part C: Open Access)
The importance of well-designed armour for mitigating threat to life cannot be overemphasized. Possibility of single and multi-layered configurations, various potential materials and their sequence and the gap in between makes the design of effective lightweight armour a complicated challenge. In the present work, nonlinear finite element analysis is used to find the ballistic performance of various combinations of composite bi-layered armours of Weldox 460 E, AA7075-T6, and SiC impacted by blunt projectiles with velocities ranging from 100 - 400 m/s. The material models employed to mimic material behaviour that accommodate high strain rates, plastic deformations and the shockwave phenomenon associated with ballistic impacts are JH1,  JC, and SCG. The ballistic performance and the prevailing failure modes for each combination are observed and validated using experimental results. To help improve the design of armour, the various combinations are subjected to a range of test conditions, ranked in terms of weight and their complete ballistic profile is presented. It is found that ceramic front plate proves to be advantageous in improving the ballistic performance, which makes one of the SiC - AA7075 bi-layered composite plates the lightest of the lot. Furthermore, the best AA7075 - Weldox combination also outperformed monolithic Weldox plate in ballistic performance as well as in weight reduction, having the additional merit of being the configuration with the smallest thickness.